ChemInform Abstract: Using Biotic Ligand Models to Predict Metal Toxicity in Mineralized Systems. Issue 26 (June 2015) - Smith, Kathleen S.; Balistrieri, Laurie S.; Todd, Andrew S.
Abstract Review: 135 refs.